2009
DOI: 10.1080/07370010903034425
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Sexually Transmitted Infections in Men and Women

Abstract: Background Sexually transmitted infections (STIs) remains a serious healthcare problem costing approximately 13 billion dollars annually to treat. Men and women who contract STIs have a higher risk for reinfection and for developing human immunodeficiency virus (HIV). Determining the risk factors associated with STIs in a community would be helpful in designing culturally appropriate tailored interventions to reduce spread of STIs. Purpose The purpose of this retrospective chart review was to determine the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
4
6
0
Order By: Relevance
“…However, consistent with prior studies, we expect that such conversations will be more likely with daughters than sons. Also consistent with prior studies, we hypothesize that males will report more condom use than females (Abma and Sonnenstein 2001; Gullett et al 2009; Zimmerman et al 2007). Studies typically report that Latino adolescents use condoms less than white youth (Anderson et al 2006; Driscoll et al 2001; Espinosa-Hernandez and Lefkowiz 2009).…”
Section: Gaps and Limitations In The Literature And The Current Studysupporting
confidence: 85%
“…However, consistent with prior studies, we expect that such conversations will be more likely with daughters than sons. Also consistent with prior studies, we hypothesize that males will report more condom use than females (Abma and Sonnenstein 2001; Gullett et al 2009; Zimmerman et al 2007). Studies typically report that Latino adolescents use condoms less than white youth (Anderson et al 2006; Driscoll et al 2001; Espinosa-Hernandez and Lefkowiz 2009).…”
Section: Gaps and Limitations In The Literature And The Current Studysupporting
confidence: 85%
“…Yet, controlled by other variables such as cohabiting status, being a male was a factor positively associated with consistent condom use with any type of partner. Similar gender differences were found in other surveys conducted in Brazil 17,18,19 , and also in surveys performed in other countries 20,21,22,23 . The gender differences described in this study may be partially explained by gender issues, including the different demeanors and practices related to the sexuality of men and women 24,25,26,27 .…”
Section: Discussionsupporting
confidence: 73%
“…The way individuals perceive and respond to risk depends on the individual level of awareness and control of other influencing factors [ 11 ] and the extent to which it affects individuals health seeking behavior [ 12 , 13 ]. For instance, a facility based study revealed that more than a third of patients with prior STIs, do not perceive themselves as at risk for another STI, and choose not to use condoms [ 14 ]. Perceived risk of reinfection for STIs is an important indicator for the likelihood of preventive action to be taken by the patient.…”
Section: Introductionmentioning
confidence: 99%